2019
DOI: 10.1111/dgd.12592
|View full text |Cite
|
Sign up to set email alerts
|

Development and evolution of color patterns in ladybird beetles: A case study in Harmonia axyridis

Abstract: Many organisms show various geometric color patterns on their bodies, and the developmental, evolutionary, genetic, and ecological bases of these patterns have been intensely studied in various organisms. Ladybird beetles display highly diverse patterns of wing (elytral) color and are one of the most attractive model organisms for studying these characteristics. In this study, we reviewed the genetic history of elytral color patterns in the Asian multicolored ladybird beetle Harmonia axyridis from the classica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 94 publications
(150 reference statements)
1
18
0
Order By: Relevance
“…The pupa is an important developmental stage in holometabolous insects because it is involved in the dissolving of larval tissue and adult organ reproduction. Ando et al [3] reported that during elytral development process, the elytral primordia growth occurs in fourth instar larvae and detaches from the pupal exoskeletion and differentiation into adult elytra in the early pupal stage (24h after pupation) [22]. As demonstrated in our results, when TH and DDC were silenced in fourth instar larvae of H. axyridis, an obvious loss in melanic color of adults followed (Figure 3).…”
Section: The Crucial Synthesis Time Of Dopamine Melanin Precursor In supporting
confidence: 72%
See 3 more Smart Citations
“…The pupa is an important developmental stage in holometabolous insects because it is involved in the dissolving of larval tissue and adult organ reproduction. Ando et al [3] reported that during elytral development process, the elytral primordia growth occurs in fourth instar larvae and detaches from the pupal exoskeletion and differentiation into adult elytra in the early pupal stage (24h after pupation) [22]. As demonstrated in our results, when TH and DDC were silenced in fourth instar larvae of H. axyridis, an obvious loss in melanic color of adults followed (Figure 3).…”
Section: The Crucial Synthesis Time Of Dopamine Melanin Precursor In supporting
confidence: 72%
“…A review of melanin in H. axyridis concluded that the transcript factor gene Pannier can regulate melanin synthesis during the ontogeny process [22]. The function of Pannier promotes melanin synthesis in the expressed region and suppresses carotenoids in the ventral epidermal cell [2,3].…”
Section: The Regulation Mechanism Of Pannier On Melanin Synthesis In mentioning
confidence: 99%
See 2 more Smart Citations
“…Liu and colleagues () review recent findings of the molecular, cellular and developmental characteristics of the peripheral nervous system in various bilaterians, and discuss its evolutionary history. Ando and Niimi () review the historical background of color patterns in the Asian multicolored ladybird beetle, Harmonia axyridis —from the results of classic genetic studies to their recent findings—and discuss various aspects of color pattern formation in insects, including its development, evolution, and ecology. Miura () examines the role of juvenile hormone in developmental phenotypic plasticity in a wide range of taxonomic groups, including insects and daphnids.…”
mentioning
confidence: 99%